Regulation mechanism of curcumin mediated inflammatory pathway and its clinical application: a review - Meihua Liu; Jingyi Wang; Zhen Song; Yong Pei (Frontiers in Pharmacology)
Curcumin, a natural polyphenolic compound derived from Curcuma longa, has shown great potential in the prevention and treatment of chronic inflammatory diseases due to its significant antioxidant and anti-inflammatory properties. This article aims to systematically review the anti-inflammatory molecular mechanism, clinical application prospects and challenges of curcumin. By searching the databases of Web of Science, PubMed, Google Scholar and CNKI, and integrating the latest research progress, it was found that curcumin exerted its core anti-inflammatory effects mainly by inhibiting the activation of nuclear factor-κB (NF-κB) signaling pathway, regulating the mitogen-activated protein kinase extracellular signal-regulated kinase (ERK) phosphorylation cascade, and regulating the Janus kinase/signal transducer and activator of transcription (JAK/STAT) pathway. Pharmacological studies have confirmed the therapeutic value of curcumin in a variety of inflammation-related diseases, including neurodegenerative diseases, inflammatory bowel disease, atherosclerosis, diabetes and tumors. Although curcumin has good safety and extensive sources, its inherent low bioavailability severely limits its clinical application. This review points out that combining cutting-edge technologies such as new nano-delivery systems, optimizing the delivery efficiency of curcumin and exploring its anti-inflammatory mechanism in depth are the focus of future research, which is expected to promote it to become a more effective clinical anti-inflammatory drug.